Evaluating Translanguaging Practices in Bilingual Classrooms - Magdalena Kartikasari Tandy Rerung (Journal of English Language and Culture, 2017)
The debate over whether English language classrooms should include or exclude students’ native language has been controversial issue for a long time (Brown, 2000). In order to overcome this situation, several studies have been conducted to find out the students’ perception toward the monolingual or bilingual approach in their classroom. It was started in the 1990s where mother tongue was attached in the language classroom. Auerbach (1993) stated that “Starting with the first language (L1) provides a sense of security and validates the learners’ lived experiences, allowing them to express themselves. Auerbach further reports that the use of L1 shows positive results among researchers and learners, Furthermore, the use of L1 in the classroom apparently help students to understand several tasks such as “language analysis, presenting grammar rules, discussing cross-cultural issues, giving instructions, explaining errors and checking comprehension”. Translanguaing in this case offers a better solution for learners who are still hesitating whenever they want to communicate in English. García(2009) explains the term as “the act” used by bilinguals in order to communicate ideas effectively by autonomously selecting their own words and language expressions. The following research would like to conduct further observation into more specific topic under translanguaging. The main focus is to analyze how lecturers deliberately send their knowledge by translanguaging. The grammar class itself would be selected for observing the following phenomena since there are some rules and forms of English structure needs to be explain in details. The process of translanguaging in this case will probably provide a way for the lecturer and students to build a bilingual environment in order to understand the message clearer. The observers will record the strategies applied by the lecturer whenever he switches the language from English to Bahasa Indonesia purposely. Keywords: translanguaging, bilingual approach